The Effect of Public Sector Accounting Implementation to Prevent Fraud in the Public Sector in the Digital Era at PT. PLN UP3 Binjai - Ginting, Berupilihen Br; Hou, Amin; Pakpahan, Dewi Rafiah; Chaniago, Sabarudddin; Amanda, Diska (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study supposed to determine the effect of the application of public sector accounting to prevent fraud in the public sector in the digital era at Pt. Pln Up3 Binjai The method used by the author in this research is This research uses qualitative descriptive research methods. This qualitative descriptive research is to determine the role of public sector accounting to prevent fraud in the public sector in the digital era at PT. PLN Up3 Binjai. This descriptive study aims to provide researchers with a history or to describe aspects relevant to the phenomenon of attention from the perspective of an organization. The type of data the author uses in this research is qualitative data. This qualitative data is obtained from direct interviews with the Internal Supervisory Unit (SPI) regarding the Role of the Internal Supervisory Unit in fraud prevention at PT PLN UP3 Binjai. The results of the conclusions in this study are the first characteristics of fraud in the public sector that occur in the digital era, including the use of misconceptions about the role of digital technology in carrying out the duties of public accountants, utilizing digital technology to optimize opportunities for fraud, taking advantage of problems in human error and lack of knowledge in the use of digital technology, using digital technology products. Furthermore, the application of Public Sector Accounting can prevent fraud in the public sector in the digital era if implemented by considering factors that affect fraud, such as performance accountability, and accompanied by the application of fraud prevention methods which include technical strategies, two paradigm approaches, and preventive strategies.